Evaluation of antioxidative and antitumor activities of extracted flavonoids from Pink Lady apples in human colon and breast cancer cell lines. Issue 12 (29th September 2015) - Yang, Shufang; Zhang, Haisheng; Yang, Xingbin; Zhu, Yilin; Zhang, Min
Abstract : Extracted flavonoids from Pink Lady apples were proved to be good food based medicines for anti-cancer effects through their ability to induce tumor cell apoptosis. Abstract : The antioxidative and anticancer effects of extracted flavonoids from Pink Lady apples on human colon cancer LoVo cells and breast cancer MCF-7 cells were evaluated. It was found that the antioxidative property of the peel-flavonoids (Peel-F) was more effective than that of the flesh-flavonoids (Flesh-F). Meanwhile, both the Peel-F and Flesh-F can inhibit cancer cell growth in a dose-dependent manner, with the IC50 values of 110.33 ± 2.52 mg mL −1 and 378.14 ± 1.64 mg mL −1 for LoVo cells and 58.42 ± 1.39 mg mL −1 and 296.06 ± 3.71 mg mL −1 for MCF-7 cells. This led to the conclusion that the Peel-F were more effective against cancer cells than the Flesh-F, and that the scavenging ROS effects were significantly higher in the Peel-F in vitro . Moreover, we also found that the generation of ROS is a critical mediator in apple flavonoid-induced cell apoptosis and the induction effect of the Peel-F was significantly higher than that of the Flesh-F.